Metabolomics as new tool in pharmacognosy - Khatib, Alfi (2019)
A latest definition of pharmacognosy includes data pooling obtained from system biology and chemo-informatics, This approach requires a holistic and comprehensive analysis of metabolites in samples which is called metabolomics. Some application of this approach in pharmacognosy lies in 3 areas as follows: - Analysis of known bio-active compounds and screening of metabolites in the extracts prior to isolation of unknown bio-active compounds. - Analytical tool in quality control and process optimization of herbal products based on the fingerprint of their metabolites. - Comprehensive bio-activity and toxicity evaluation of the herbal products. In this lecture, several medicinal Malaysia herbs are used as an example such as Clinacanthus nutans, Momordica charantia, and Psychotria malayana.